The Antarctic Peninsula under present day climate and future low, medium-high and very high emissions scenarios - Davies, Bethan J.; Atkinson, Angus; Banwell, Alison F.; Brandon, Mark; Caton Harrison, Thomas; Convey, Peter; De Rydt, Jan; Dodds, Klaus; Downie, Rod; Edwards, Tamsin L.; Gilbert, Ella; Hubbard, Bryn; et al. (Frontiers in Environmental Science, 2026)
The Antarctic Peninsula is warming rapidly, with more frequent extreme temperature and precipitation events, reduced sea ice, glacier retreat, ice shelf collapse, and ecological shifts. Here, we review its behaviour under present-day climate, and low (SSP 1–2.6), medium-high (SSP 3–7.0) and very high (SSP 5–8.5) future emissions scenarios, corresponding to global temperature increases of 1.8 °C, 3.6 °C and 4.4 °C by 2100. Higher emissions will bring more days above 0 °C, increased liquid precipitation, ocean warming, and more intense extreme weather events such as ocean heat waves and atmospheric rivers. Surface melt on ice shelves will increase, depleting firn air content and promoting meltwater ponding. Under the highest emission scenario, collapse of the Larsen C and Wilkins ice shelves is likely by 2100 CE, and loss of sea ice and ice shelves around the Peninsula will exacerbate the current trends of land-ice mass loss. Collapse of George VI Ice Shelf by 2300 under SSP 5–8.5 would substantially increase sea level contributions. Under this very high emissions scenario, sea level contributions from the Peninsula could reach 7.5 ± 14.1 mm by 2100 CE and 116.3 ± 66.9 mm by 2300 CE. Conversely, under the lower emissions scenarios, the Antarctic Peninsula’s sea ice remains similar to present, and land ice is predicted to undergo only minor grounding line recession and thinning. Changes in sea surface temperatures and the change from snow to rain will impact marine and terrestrial biota, altering species richness and enhancing colonisation by non-native species. Ranges of key species such as krill and salps are likely to contract to the south, impacting their marine vertebrate predators. These changing conditions will also influence Antarctic Peninsula research, fisheries, tourism, infrastructure and logistics. The future of the Peninsula depends on the choices made today. Limiting temperatures to below 2 °C, and as close as possible to 1.5 °C (by following the SSP 1–1.9 or 1–2.6 scenarios), combined with effective governance, will result in increased resilience and relatively modest changes. Any higher emissions scenarios will damage pristine systems, cause sustained, irreversible ice loss on human timescales, and spread to Antarctic regions beyond the Peninsula.